OCR A2 psychology - Bainbridge, Alan; Collier, William; Latham, Sandra; Lintern, Fiona; Middleton, Sarah; Saunders, Bryan (Oxford : Heineman Educational, 2008)
Accompaying CD-ROM in pocket at the rear of book.
On cover: ExamCaf ČD-ROM inside.
Keywords: Psychology -- Study and teaching (Secondary)